Pengaruh Kompensasi Finansial dan Nonfinansial terhadap Komitmen Karyawan - Farla, Wita; Diah, Yuliansyah M; Bakri, Supardi A (University of Merdeka Malang, 2019)
The aims of this study are to determine how the effect of financial and non-financial compensation on employee commitment both partially and simultaneously. This research is a causality study with the quantitative data. Data is collected using a questionnaire which Â tested for its feasibility by validity and reliability testing. The population in this study are UMKM employees in Palembang with a sample size of 100 respondents. Data is analyzed using descriptive analysis and multiple linear regression analysis. This results of this study show that financial compensation has no effect on employee commitment while non-financial compensation has effect on employee commitment.https://doi.org/10.26905/jmdk.v7i1.2775